2021
DOI: 10.3389/fonc.2021.666826
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Cell Cycle–Related and Immunity-Related Biomarker Signatures to Improve the Prognosis Prediction of Lung Adenocarcinoma

Abstract: BackgroundLung adenocarcinoma (LUAD) is a leading malignancy and has a poor prognosis over the decades. LUAD is characterized by dysregulation of cell cycle. Immunotherapy has emerged as an ideal option for treating LUAD. Nevertheless, optimal biomarkers to predict outcomes of immunotherapy is still ill-defined and little is known about the interaction of cell cycle-related genes (CCRGs) and immunity-related genes (IRGs).MethodsWe downloaded gene expression and clinical data from TCGA and GEO database. LASSO r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…Based on eight cell cycle-immunity-related genes, Chen et al. ( 26 ) constructed a prognosis model to predict the OS in Lung adenocarcinoma (LUAD) samples, and this model was correlated with immune cell infiltration. Similarly, using bioinformatics analysis, another concurrent study has shown that a G2/M checkpoint-related signature composed of five genes (MARCKS, CCNF, MAPK14, INCENP, and CHAF1A) was connected with the prognosis of gastric cancer (GC) patients ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on eight cell cycle-immunity-related genes, Chen et al. ( 26 ) constructed a prognosis model to predict the OS in Lung adenocarcinoma (LUAD) samples, and this model was correlated with immune cell infiltration. Similarly, using bioinformatics analysis, another concurrent study has shown that a G2/M checkpoint-related signature composed of five genes (MARCKS, CCNF, MAPK14, INCENP, and CHAF1A) was connected with the prognosis of gastric cancer (GC) patients ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wai Hoong Chang et al explored the prognostic value of DNA repair genes in pan-cancer and confirmed that DNA repair genes were associated with dysregulation of cell cycle and hypoxia ( Chang and Lai, 2019 ). Fangyu Chen et al integratedly investigated the predictive value of cell cycle-related and immune-related genes in lung adenocarcinoma ( Chen et al, 2021b ). HCC can be divided into two subtypes with different molecular and clinical characteristics based on DNA damage repair related genes ( Lin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The predictive power of the CCP gene-derived signatures was also confirmed in early-stage lung adenocarcinoma [ 37 , 38 ]. Furthermore, Chen and colleagues recently developed a risk-predicting signature with eight immunity-related cell cycle genes [ 41 ]. These findings indicate the reliability of predicting prognosis with CCP signatures in cancer.…”
Section: Discussionmentioning
confidence: 99%